Marrow Hematopoietic Stem Cells Revisited: They Exist in a Continuum and are Not Defined by Standard Purification Approaches; Then There are the Microvesicles - Quesenberry, Peter J.; Goldberg, Laura; Aliotta, Jason; Dooner, Mark (Frontiers in Oncology, 2014)
Current concepts of hematopoiesis are encompassed in a hierarchical stem cell model. This developed initially from studies of colony-forming unit spleen and in vitro progenitors for different cell lineages, but then evolved into a comprehensive model of cells with different in vivo differentiative and proliferative potential. These cells were characterized and purified based largely on expression of a variety of lineage-specific and stem cell-specific surface epitopes. Monoclonal antibodies were bound to these epitopes and then used to physically and fluorescently separate different classes of these cells. The gold standard for the most primitive marrow stem cells was long-term multilineage repopulation and renewal in lethally irradiated mice. Progressive work seemed to have clonally defined a Lineage negative (Lin−), Sca-1+, c-kit+, CD150+ stem cell with great proliferative, differentiative, and renewal potential. This cell was stable and in the G0 phase of cell cycle. However, continued work in our laboratory indicated that the engraftment, differentiation, homing, and gene expression phenotype of the murine marrow stem cells continuously and reversibly changes with passage through cell cycle. Most recently, using cycle-defining supravital dyes and fluorescent-activated cell sorting and S-phase-specific tritiated thymidine suicide, we have established that the long-term repopulating hematopoietic stem cell is a rapidly proliferating, and thus a continually changing cell; as a corollary it cannot be purified or defined on a clonal single cell basis. Further in vivo studies employing injected and ingested 5-Bromodeoxyuridine (BrdU), showed that the G0 Lin-Sca-1, c-kit+ Flt3− cell was rapidly passing through cell cycle. These data are explained by considering the separative process: the proliferating stem cells are eliminated through the selective separations leaving non-representative dormant G0 stem cells. In other words, they throw out the real stem cells with the purification. This system, where the marrow stem cell continuously and reversibly changes with obligate cell cycle transit, is further complicated by the consideration of the impact of tissue microvesicles on the cell phenotypes. Tissue microvesicles have been found to alter the phenotype of marrow cells, possibly explaining the observations of “stem cell plasticity.” These alterations, short-term, are due to transfer of originator cell mRNA and as yet undefined transcription factors. Long-term phenotype change is due to transcriptional modulation; a stable epigenetic change. Thus, the stem cell system is characterized by continuous cycle and microvesicle-related change. The challenge of the future is to define the stem cell population.